2015
DOI: 10.2217/nnm.14.212
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology in Bladder Cancer: Current State of Development and Clinical Practice

Abstract: Nanotechnology is being developed for the diagnosis and treatment of both nonmyoinvasive bladder cancer (NMIBC) and invasive bladder cancer. The diagnostic applications of nanotechnology in NMIBC mainly focus on tumor identification during endoscopy to increase complete resection of bladder cancer while nanotechnology to capture malignant cells or their components continues to be developed. The therapeutic applications of nanotechnology in NMIBC are to reformulate biological and cytotoxic agents for intravesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 86 publications
0
19
0
1
Order By: Relevance
“…Nanomedicine has emerged as promising diagnostic and therapeutic modalities in the management of cancer. However, no such drugs have been approved for bladder cancer [13]. We previously reported the development of non-cross-linked PNM that represents a significant development compared to free PTX in Cremophor EL/ethanol (Taxol®).…”
Section: Discussionmentioning
confidence: 99%
“…Nanomedicine has emerged as promising diagnostic and therapeutic modalities in the management of cancer. However, no such drugs have been approved for bladder cancer [13]. We previously reported the development of non-cross-linked PNM that represents a significant development compared to free PTX in Cremophor EL/ethanol (Taxol®).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent work has been reported in which nanoparticles are employed in conjunction with cystoscopy to improve the recognition of tumours, for example distinguishing at lesions from non-malignant cells, yet though outcomes are positive, there is still an invasive element to the procedure. 50 Finally, in a recent paper by Aggio et al, it was reported that a GC-sensor was able to distinguish in urine prostate cancer from controls, bladder cancer from controls, and bladder cancer from prostate cancer via an in-house data processing and analysis pipeline reporting very high ([90%) accuracies, sensitivities and specicities. 51 It was stated that "different VOCs are associated with the two urological disorders" however it must be suggested that it is very likely that there will also be the same VOCs present in both cancers.…”
Section: Diagnostic Potentialmentioning
confidence: 99%
“…There are few different approaches such as the use of hydrogels and mucoadhesive gels, which help to maintain the optimal drug concentration in the bladder [ 120 , 121 ]. Liposomes and nanoparticles can be applied to selectively and efficiently deliver the chemotherapeutics to the tumor site and increase the specificity of photosensitizers used in the photodynamic therapy [ 122 ]. Additionally, chemical compounds such as DMSO and hyaluronidase have been shown to upregulate the diffusion and tissue absorption of cytostatics [ 119 ].…”
Section: Electrochemotherapymentioning
confidence: 99%